GRKs and β-Arrestins: “Gatekeepers” of Mitochondrial Function in the Failing Heart - Sorriento, Daniela; Gambardella, Jessica; Fiordelisi, Antonella; Iaccarino, Guido; Illario, Maddalena (Frontiers in Pharmacology, 2019)
Mitochondrial regulation of energy production, calcium homeostasis, and cell death are critical for cardiac function. Accordingly, the structural and functional abnormalities of these organelles (mitochondrial dysfunction) contribute to developing cardiovascular diseases and heart failure. Therefore the preservation of mitochondrial integrity is essential for cardiac cell survival. Mitochondrial function is regulated by several proteins, including GRK2 and β-arrestins which act in a GPCR independent manner to orchestrate intracellular signaling associated with key mitochondrial processes. It is now ascertained that GRK2 is able to recover mitochondrial function in response to insults. β-arrestins affect several intracellular signaling pathways within the cell which in turn are involved in the regulation of mitochondrial function, but a direct regulation of mitochondria needs further investigations. In this review, we discuss the recent acquisitions on the role ofGRK2 and β-arrestins in the regulation of mitochondrial function.